A public theologian : a critical study of J. Wentzel van Huyssteen’s postfoundationalist facilitation of interdisciplinarity - Loubser, G. M. H. (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2012.